Utilization of the Accelerometer Sensor in Android Smartphones Development of Ground Movement Detection Tools in Areas Landslide Prone Based on the Internet of Things - handayani, eka sri; suroyo, heri (Jurnal Informatika Universitas Pamulang, 2023)
The result of this research is an Internet of Things (IoT) program that utilizes the accelerometer sensor on Android smartphones as a tool for detecting ground movement in landslide-prone areas. If the sensor indicates a change in its coordinates, it will be used as an indication of ground movement on the accelerometer sensor. Meanwhile, the gyroscope sensor detects vibrations, and the program will send notifications as a sign of ground movement. Overall, the development of this landslide movement detection device in landslide-prone areas employs the Research and Development (R&D) methodology. The Research and Development method aims to produce specific products and test the effectiveness of these products. The development method for the ground movement system utilizes a prototype method to observe and comprehend how the application functions. The results of this research demonstrate that the accelerometer sensor on Android smartphones can produce sufficiently accurate data for detecting ground movement. Integration with IoT technology opens opportunities for developing an early warning system that is effective and responsive to the potential landslide disasters. It is hoped that this research can provide a significant contribution to the development of more advanced ground movement detection systems in the future.